PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF STUDENTS RESEARCH SKILLS IN THE USE OF THE LABORATORY IN BIOLOGY LESSONS - Tadjiyev, X.M. (Journal of Learning on History and Social Sciences, 2025)
Objective: To examine the methodological foundations underpinning the formation of the competence "Observation, understanding, and explanation of biology through laboratory works and experiments." Method: A qualitative analysis was conducted, reviewing current pedagogical strategies, curriculum designs, and laboratory practices to assess their effectiveness in fostering scientific inquiry and conceptual understanding. Results: The findings demonstrate that a structured approach to laboratory work significantly enhances students' abilities to observe, comprehend, and articulate biological phenomena, thereby establishing a critical basis for the development of broader professional competencies. Novelty: This research offers an innovative framework that integrates theoretical insights with practical applications, providing a novel contribution to biology education by linking laboratory-based activities with the cultivation of essential research skills.